Sustainable development of industrial enterprises in the basis of a new form of economic activity organisation - O. E. Astafyeva (Вестник университета)
This article examines a new form of economic activity organisation for industrial enterprises in the context of the digital transformation of the economy. The analysis of networking in the cluster and economic approaches has allowed us to identify the guiding principles of interaction between economic actors, and the resulting effects and “values”. The platform education proposed by the author as an organisational and economic activity form is the digital ecosystem component, which is a spatial and temporal environment for the functioning of enterprises. A scheme for assessing data and process management in this ecosystem has been developed using the metrics proposed by the author. This scheme reflects the production-logistics chain formed in the framework of the actors’ integration in the digital ecosystem.